Implementasi kegiatan senam sehat gembira dalam meningkatkan kemampuan motorik kasar anak usia dini di RA Sirajut thalibin racek tiris probolinggo: Pendahuluan, metode penelitian, hasil penelitian, pembahasan, simpulan dan saran, refrensi - HALIMATUS SA’DIYAH; ENDAH TRI WISUDANINGSIH; TERZA TRAVELANCYA DP (incrementapedia, 2023)
Implementation of happy healthy gymnastic activities is very important for the gross motor development of early childhood because every movement can build muscle endurance, for example: wrists, back, arms and so on. RA Sirajut Thalibin conducts healthy gymnastic activities for joy, the implementation is carried out once a week, namely on Wednesdays. Happy healthy gymnastics besides improving gross motor skills also affects children's intelligence, one of which is kinesthetic intelligence, the advantages of a child who has kinesthetic intelligence tends to memorize faster and be able to complete tasks well. This study uses qualitative research with a descriptive research design. Collecting data in this study using interview techniques, observation, and documentation. The results of research at RA Sirajut Thalibin are as follows: 1). Implementation of Joyful Healthy Gymnastic Activities in Improving Gross Motor Skills of Early Children at RA Sirajut Thalibin Racek-Tiris-Probolinggo, begins with warm-up movements, core movements, and cool-down movements. Through these activities the child's body, legs and hands are well coordinated over time. 2). Supporting factors such as the condition of the child who is very enthusiastic and passionate about doing gymnastics. 3). Inhibiting factors such as weather sometimes does not support such as rain and infrastructure that experiences technical problems